The Effectiveness of Ecoviar (Ecosystem via Augmented Reality) Learning Media in Enhancing Students’ Computational Thinking and Scientific Literacy - Cendani, Tinezia; Kristanto, Andi; Mariono, Andi; Zakaria, Aminudin; Nisa', Khoirun (Universitas Negeri Surabaya, 2026)
Objective: The objective of this study was to assess the effectiveness of ECOVIAR (Ecosystem via Augmented Reality) learning media in improving elementary school students' Computational Thinking and scientific literacy skills on ecosystem material. Method: A quasi-experimental design with a non-equivalent control group design was used in this study. A total of 60 fifth-grade students participating in the experimental class and the control class were used as the research sample. The experimental class was given treatment using ECOVIAR media, while the control class underwent conventional learning. Data were collected using a validated long-response test to measure Computational Thinking and scientific literacy. Data analysis was calculated using a normality test, a homogeneity test, and an independent sample t-test. Results: The findings indicated no significant difference in the initial abilities between the two groups (Sig. > 0.05). However, significant differences were found in the post-test results for both computational thinking (Sig. = 0.002 < 0.05) and scientific literacy (Sig. = 0.000 < 0.05). It is concluded that students taught using ECOVIAR media achieved significantly higher learning outcomes compared to those in the conventional learning group. Novelty: The development and utilization of Augmented Reality media in learning specifically designed for the ecosystem of learning materials with a focus on improving Computational Thinking and scientific literacy is a novelty in this study, because it is still rarely studied simultaneously in elementary school expansion.